Self-related motivational aspects of hindsight bias in soccer athletes - Li, Tianpei; Guo, Haifeng; Hwang, Jin (Frontiers in Sports and Active Living, 2025)
PurposeHindsight bias is known to hinder people from learning and make people too adventurous in future decisions. The influence of hindsight bias on athletes, however, has not been widely and extensively investigated. Thus, the purpose of this study is to examine self-related motivational aspects of hindsight bias in a sports context.MethodQuestionnaires were completed by 84 soccer players in a retrospective-design study. Respondents were divided into winning team members vs. losing team members and playing members vs. nonplaying members to assess the culpability for a negative outcome and outcome controllability.ResultsTwo-way repeated-measures ANOVA revealed significant hindsight bias for the expected match score regardless of team and player factors. In terms of player factors, playing members of the losing team and nonplaying members of the winning team increased their confidence levels for the expected match score. In terms of team factors, winning team members increased their confidence levels for the expected winning team. The reverse was true for losing team members.ConclusionsPlaying members of a losing team used retroactive pessimism and showed greater hindsight bias. Winning team members showed greater hindsight bias, consistent with previous findings that people show hindsight bias for their own good performances. The results are further discussed in light of outcome controllability, expertise, and disappointment.